Functional Proteins Involved in Regulation of Intracellular Ca2+ for Drug Development: Chronic Nicotine Treatment Upregulates L-Type High Voltage-Gated Calcium Channels - Masashi Katsura; Seitaro Ohkuma (Elsevier, 2005)
Neurochemical mechanisms underlying drug dependence and withdrawal syndrome remain unclear. In this review, we discuss how chronic nicotine exposure to neurons affects expression of diazepam binding inhibitor (DBI), an endogenous anxiogenic neuropeptide supposed to be a common substance participating drug dependence, and function of L-type high voltage-gated Ca2+ channels (HVCCs). We also discuss the functional interaction between DBI and L-type HVCCs in nicotine dependence. Both DBI levels and [45Ca2+] influx significantly increased in the brain from mice treated with nicotine for long term, which was further enhanced after abrupt cessation of nicotine and was abolished by nicotinic acetylcholine receptor (nAChR) antagonists. Similar responses of DBI expression and L-type HVCC function were observed in cerebral cortical neurons after sustained exposure to nicotine. In addition, increased DBI expression was inhibited by antagonists of nAChR and L-type HVCCs. Sustained exposure of neurons to nicotine significantly enhanced expression of α1 and α2/δ1 subunits for L-type HVCCs and caused an increase in the Bmax value of [3H]verapamil binding to the particulate fractions. Therefore, it is concluded that the alterations in DBI expression is mediated via increased influx of Ca2+ through upregulated L-type HVCCs and these neurochemical changes have a close relationship with development of nicotine dependence and/or its withdrawal syndrome. Keywords:: anxiety, diazepam binding inhibitor, nicotine dependence, L-type high voltage-gated Ca2+ channel, withdrawal syndrome